EXTRACT OF MINDI LEAF ( MELIA AZEDARACH L) - Gusti Wangi Permana (Perhimpunan Kesehatan Holistik Indonesia, 2020)
The interest of the Indonesian people to use natural ingredients as traditional medicines that are easily available and affordable is the cause of the need for research on the active chemical substances contained in plants. One of the plants that can be used as medicine is the mindi plant (Melia azedarach L.) which is used by the community as a deuretic (urinary laxative), worm laxative,laxative, and so on. Chemical content contained in mindi leaves is achaloid parasina, routine flavonoids, bitter substances, saponins, tannins, steroids, and kaemferol.